Self-harm among post-natal mothers in Northwest Ethiopia: Implication for policy and practice - Tiguh, Agumas Eskezia; Wondie, Kindu Yinges; Gessesse, Dereje Nibret; Tsega, Nuhamin Tesfa; Aklil, Mastewal Belayneh; Temesgan, Wubedle Zelalem; Abegaz, Marta Yimam; Anteneh, Tazeb Alemu; Tibebu, Nebiyu Solomon; Alemu, Haymanot Nigatu; Haile, Tsion Tadesse; Seyoum, Asmra Tesfahun; et al. (Frontiers in Public Health, 2022)
Introduction: Self-harm is a global public health concern affecting thousands of women. However, it is an under-reported and neglected aspect of maternal health, particularly in developing countries. In Ethiopia, there is a paucity of evidence regarding self-harm, and attention is rarely given. Therefore, this study was aimed to assess the magnitude of self-harm and associated factors among postnatal mothers in Gondar city, northwest Ethiopia. Method: In Gondar city, a community-based cross-sectional study was conducted from July 1st to August 30th, 2021. A cluster sampling technique was performed to select 858 women who gave birth in the last 12 months. The data were collected using a structured questionnaire through face-to-face interviews. Data were entered into EPI data version 4.6 and exported to SPSS 25 for analysis. The multivariable logistic regression analysis was fitted to identify factors associated with the outcome variable. The level of significant association was determined at a p-value of ≤ 0.05. Result: The proportion of post-natal self-harm was found to be 8.5% (95% CI: 6.7,10.5). Having lower family income (AOR: 2.41, 95% CI: 1.05,5.56), having unplanned pregnancy (AOR: 2.70, 95% CI: 1.53,4.79), experiencing adverse birth outcomes (AOR: 3.11, 95% CI: 1.10,8.83), birth not attended by health provider (AOR: 4.15, 95% CI :1.76,9.79), experiencing intimate partner violence (AOR: 1.93, 95% CI: 1.12,3.32) and poor decision-making power (AOR: 1.70, 95% CI :1.02, 2.84) were the variables significantly associated with self-harm. Conclusion This study revealed that the proportion of post-natal self-harm was prevalent. Factors like family monthly income, planned pregnancy, birth outcome, birth assistant, intimate partner violence, and decision-making power show an association with maternal self- harm. Antenatal and postnatal self–harm screening as part of the continuum of maternal health care is important. Self-harm is also a danger for women who have experienced intimate partner violence or have low socioeconomic economic status, all of which require exceptional mental-health assessment.